Placental Acretism At The Maternal Perinatal National Institute - Gonzales-Carrillo, Oswaldo (2017)
Objective. To determine the clinical and management features of placenta accreta in the period between 2014 and 2014. Materials and methods. We reviewed the cases of placenta accreta retrospectively. Clinical features, diagnosis, medical and surgical management were defined.